2011
DOI: 10.1620/tjem.224.13
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Demethylation of Interferon-.GAMMA. Gene Promoter in Peripheral Blood Mononuclear Cells Is Associated with Acute-on-Chronic Hepatitis B Liver Failure

Abstract: Acute-on-chronic hepatitis B liver failure (ACHBLF) refers to liver failure occurring in patients with chronic hepatitis B (CHB) related liver diseases. Interferon-γ (IFN-γ) plays an important role in the exacerbation of liver function. However, the exact mechanism, by which IFN-γ mediates ACHBLF, is not fully understood. Forty patients with ACHBLF, fifteen patients with CHB and ten healthy controls were included in this present study. ELISA was performed to measure the level of serum IFN-γ. The methylation st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Previous studies have shown that the presence of the +874T and A alleles is associated with high and low IFN-c expression, respectively [16,34]. Furthermore, the plasma IFN-c concentration was found to be significantly decreased in patients with chronic hepatitis B relative to healthy controls [15,35]. Additionally, Chen et al found that the level of Th1-type cytokines (including IFN-c) was higher and that of Th2-type cytokines (IL-4, IL-6, and IL-10) was lower in responders than in nonresponders after HBV antiviral treatment [36].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies have shown that the presence of the +874T and A alleles is associated with high and low IFN-c expression, respectively [16,34]. Furthermore, the plasma IFN-c concentration was found to be significantly decreased in patients with chronic hepatitis B relative to healthy controls [15,35]. Additionally, Chen et al found that the level of Th1-type cytokines (including IFN-c) was higher and that of Th2-type cytokines (IL-4, IL-6, and IL-10) was lower in responders than in nonresponders after HBV antiviral treatment [36].…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have shown that the presence of the +874T and A alleles is associated with high and low IFN‐γ expression, respectively . Furthermore, the plasma IFN‐γ concentration was found to be significantly decreased in patients with chronic hepatitis B relative to healthy controls . Additionally, Chen et al .…”
Section: Discussionmentioning
confidence: 91%
“…In infectious diseases, a growing number of studies have shown that DNA methylation plays a critical role in regulating the differentiation of immune cells and the expression of cytokines (12)(13)(14)(15). The methylation level of several genes, like IL-4, IL-10, IFN-γ and TNF-α had great changes with infection of bacterial and virus (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…IFN-␥ can be predominantly released by macrophages, NK cells and T cells, and fulfills anti-viral and proinflammatory functions [21]. Several groups have described the upregulation of IFN-␥ in virus-or chemicalassociated ALF [22,23] and in vivo administration of anti-IFN-␥ antiserum displayed a protective effect by markedly suppressing the circulating IFN-␥ and TNF-␣ [23].…”
Section: The Critical Roles Of Kcs In the Pathogenesis Of Alfmentioning
confidence: 99%